Advisory Committee on S&T for ACP Agricultural and Rural Development meets on November 23-26, 2004 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
CTA will convene the 3rd Meeting of the Advisory Committee on S&T for ACP Agricultural and Rural Development in Wageningen, The Netherlands November 23 - 26, 2004.